Sandstone as an architectural expression. Architectural-historical research at the Royal Palace (Bulletin KNOB, 2013)
Over the past few years (2006-2011), the former town hall of Amsterdam, which has been in use as Royal Palace since 1808, was restored. During the restoration work studies of both the building history and of the colour history were conducted. This research has yielded important information about the original colour scheme of the interior and has led to the conclusion that sandstone, specifically its colour, was an important element in the architectural expression. The atmosphere of the current interior of the Royal Palace is now defined by alterations made in the early 19th century and a number of restorations carried out in the 20th century. Especially on the first floor this means that the original finish in sandstone colour is all but gone. By contrast, on the ground floor the use of sandstone as part of the original finish has been preserved in general. The sandstone, now partly painted white, was originally unpainted, as is evident from the very finely chiselled finish.The research has also shown that some rooms on the first floor, such as the Oudraadzaal, the Mozeszaal, the Schepenkamer and the former town clerk’s office have brick vaults that were originally finished in sandstone colour. It was also concluded that the massive sandstone vaults of the galleries were originally also unpainted.This original colour scheme contrasts with the current white appearance of the vaults on the first floor. The original interior finish was preserved best in the Rekenkamer. This room is not vaulted but has a coffered oak ceiling. The blond-brown colour scheme of this ceiling is in harmony with the yellow-grey sandstone elements of the interior. One cannot help but notice that this light colour of the ceiling differs from the other coffered ceilings on the first floor. Research has shown that the darker colour of the other coffered ceilings is a result of a restoration approach of the 20th century. The primary blonde-brown colour of the coffered ceilings was originally also in harmony with the sandstone-coloured vaults in the other rooms on the first floor.As the town hall was converted to Royal Palace in the beginning of the 19th century, followed by a number of restorations in the 20th century, the original colour scheme of the interior had all but disappeared and with it the knowledge of these elements.